Tetrameric and dimeric malate dehydrogenase isoenzymes in Trypanosoma cruzi epimastigotes - Reynoso Hunter, Giselle (2000)
Two malate dehydrogenase isoforms, named MDH1 and MDH2, have been purified to homogeneity from Trypanosoma cruzi epimastigotes. Both enzymes consist of subunits with a molecular mass close to 33 kDa; native molecular mass determination by gel filtration, however, indicated that MDH1 is a dimer, whereas MDH2 is a tetramer. Both isoforms did not cross-react immunologically. The N-termini of both MDH isoforms and several tryptic peptides of MDH1 (amounting to about one third of the complete molecule) have been sequenced by automated Edman degradation. The tryptic digests of both enzymes have also been analysed by mass spectrometry (MALDI-TOF MS). The apparent K(m) values in both directions of the reaction have been determined, as well as the possible inhibition by excess of the substrate oxaloacetate. The sequence data, together with the pI values and the presence or absence of oxaloacetate inhibition indicate that the dimeric MDH1 is the mitochondrial isoenzyme, whereas the tetrameric MDH2 is the glycosomal isoenzyme. No evidence was found for the presence of a cytosolic isoform. (C) 2000 Elsevier Science B.V.